2012
DOI: 10.5935/1676-4285.20120061
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment disorders in the postpartum resulting from childbirth: a descriptive and exploratory study

Abstract: Introduction: The experience of childbirth may result in the appearance of adjustment disorders (AD), jeopardizing maternal and newborn health. Aim: Check for signs of AD in mothers and their possible relationship with the birth experience. Method: This is a descriptive exploratory study. Data were collected at two moments in time: in the immediate postpartum period and between 90 to 180 days after delivery, in which we applied the Impact of Events Scale (IES). The study population consisted of 98 mothers at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
3
0
8
Order By: Relevance
“…Um estudo aponta que a experiência traumática no parto pode trazer transtornos de adaptação no puerpério à medida que influencia o estado emocional da mulher (14) .…”
Section: Discussionunclassified
“…Um estudo aponta que a experiência traumática no parto pode trazer transtornos de adaptação no puerpério à medida que influencia o estado emocional da mulher (14) .…”
Section: Discussionunclassified
“…Alguns estudos também têm apontado para outros fatores que podem influenciar o estado emocional da mulher no pós-parto, como a vivência de uma experiência traumática no parto, que pode trazer transtornos de adaptação no puerpério (19) , e a importância do suporte social para as mulheres no período perinatal, pois quanto maior a percepção de apoio social das mulheres com uma rede de apoio fortalecida, menor a chance de desenvolver sintomas depressivos (20) .…”
Section: Discussionunclassified
“…Both the issues of the companion and the type of delivery are especially related to the current model of obstetric care prevalent in most health institutions, breaking with the legal rights and the role of women in the process of childbirth and birth, which has not been a priority. 12,18 Another study showed that 49.4% of women showed some kind of inhuman treatment by health professionals, with careless practices for women expressing obstetric violence, with 66.8% of women undergoing medical procedures without their consent; 36.7% realized that they were raped; and 20.5% did not report having suffered some kind of violent practice during their care. Regarding inhuman treatment, 23.8% reported that they were prevented from having contact with the newborn, and 21.6% were criticized for crying and screaming during labor; 19.5% felt that it was impossible to express their anxieties and anxieties for fear of reprisals.…”
Section:  Obstetric Violence In the Perception Of Usersmentioning
confidence: 99%
“…This percentage meant that 55.6% of the women who had evidence of postpartum adjustment disorders, due to delivery and showed the importance of the companion in the labor and birth event, guaranteeing continuous emotional support to the parturient, a sense of security and providing a more satisfactory delivery experience. 12 Thus, studies have shown the need for a conceptualization of the issue, which should focus on women's rights, with legal mechanisms to contribute to the confrontation of obstetric violence. Therefore, it is necessary to broaden the discussions on the subject, as well as a rationale for the problem, since the studies evaluated still lack these approaches.…”
Section: Obstetric Violence: Typology Definitions and Legislationmentioning
confidence: 99%
See 1 more Smart Citation